THE OPTIMATION OF SPECTROFLOUROMETRIC METHOD FOR DETERMINATION OF MALONIC DIALDEHYDE IN HUMAN SPERM - Sudjarwo . (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2001)
Optimation of a method is an obligatory step in order one to obtain a valid and accountable data, especially when one deal with biological samples. Biological samples usually contain minute substances which sometime elicit great errors when someone try to determine its concentration. Therefore, in order to reduce those errors, optimation of a method is mandatory to be carried out. The aim of this experiment was to determine malonic dialdehyde (MDA), a product of lipid peroxidation. The optimation carried out in this experiment include the selection of wavelength of maximum absorbance, the amount of sodium thiobarbiturate, pH, the incubation period, standard curve linearity, limit of detection and quantification, accuracy and precision. The result showed that the optimum conditions of spectrofluorometric method of MDA were as follow: the excitation and emission wavelengths was 522 and 575 nm, respectively, pH of 1 and incubation period of 135 minutes. These conditions yielded correlation coefficient of standard curve of 0.9993, limit detection and quantification of 3.5146 x 10-4 mg/ml and 1.0544 x 10-3 mg/ml, respectively, an average recovery of 85.01 % and variation coefficient of 1.84 %.Key words: optimation, spectrofluorometric, sperm, malonic dialdehyde, MDA